Quality Control of Glass Bottle Drinking Water Products Using the Six Sigma Method - Prasetyowati, Erwin; Matsaini; Sofwanul Bary; Mohammad Fajar (UNIPA PRESS, 2025)
This study aims to strengthen production performance and product quality to achieve various financial and strategic goals, such as market share, competitiveness, and profitability. The problem faced by this company is in product quality control where there are still defective products that arise during the production process. Therefore, this study uses Six Sigma with the concept of Difine Measure Analysis Improve Control (DMAIC) as a step to optimize production procedures at UD. NUSAQU whose product is bottled drinking water. The focus of this study is visual of product defects in the form of cups which are divided into two, namely Grade A and Grade B, which are distinguished based on the plastic cup material used. The results of data testing show that in Grade A and Grade B, slanted lid damage has the highest level of damage, but in Grade B the results are the same as leaking cups. The DPMO value produced in Grade A is 62,633.914, while in Grade B it is 130,961.47. The smaller the DPMO value, the better the product quality. The average value of Six-Sigma for Grade A is 3.03, while Grade B is 2.63. Based on these values, it can be concluded that Grade A has better quality than Grade B, but both require improvement and enhancement efforts to achieve 6 sigma.